RUSPIN TECHNOLOGY MAKING TRAINING IN LANCANG GARAM VILLAGE - Rinaldi Mirsa; Muhammad Muhammad; Eri Saputra; Alvin Azhar Hutasuhut; Andrit Yamesa (Universitas Muhammadiyah Aceh, 2022)
Instant Panel System House Technology (RUSPIN) is one the solutions to solve the problem of high production costs and inefficient construction time accompanied by failure to meet building engineering quality requirements. This technology offers precast house frames with a panel system and bolted connections that can be installed quickly, at lower cost, and meet the technical quality of a house. Its hoped that this training could be an alternative livelihood in the area. The method used were Forum Group Discussion (FGD) followed by training on making RUSPIN as well as monitoring and evaluation. The community empowerment activity is to provide informations and skills to the Lancang garam Village community on how to make RUSPIN, so that they can develop their own business for long term and can act as a joint effort to produce the Instant Panel System Flats (RUSPIN). The conclusion of the implementation of community is to create production of RUSPIN technology in accordance with standards for developing home industries, increasing knowledge in developing small and medium enterprises. Keywords: RUSPIN, Training, Community, Livelihood.